A three years’ experience of Arteriovenous Fistula (AVF) cases in a tertiary care hospital of East Java, Indonesia: a descriptive observational study - Rafaela Andira Ledyastatin; Caesario Tri Prasetyo; Gold Sunday Palm Tampubolon; Dhihintia Jiwangga (Indonesian Vascular Access Association (IVAA), 2021)
Introduction: The incidence of end-stage renal disease (ESRD) globally is 700 million people approximately. Patients with ESRD need vascular access for hemodialysis as renal replacement therapy (RRT). Among hemodialysis access, arteriovenous fistula is considered as the most preferred form of vascular access due to its characteristics. This study aimed to to present a descriptive characteristic of arteriovenous fistula creation cases in a tertiary care hospital with a specific view of demographic parameters, fistulas' sites, type of fistulas. Methods: We conducted a descriptive study of single-center in the Department of Thoracic, Cardiac and Vascular Surgery of Dr. Soetomo Academic General Hospital Surabaya, collected data from January 1st, 2017 to December 31st, 2020. All patients who undergo arteriovenous fistula creation considered as a subject in this study. We retrieved the characteristics of the patients, the type of fistula, the site, surgical technique, and underlying disease from patients’ electronic medical data records. Results: A total of 167 patients requiring long-term hemodialysis in our center. Females were dominantly in our study with 56.9% (95). Most of AVFs were created on the left arm. Radiocephalic type of AVF was the most common arteriovenous fistula type found in 111 subjects (66.5%). The highest postoperative successful rate was found in brachiocephalic type in 78.8%, followed by radiocephalic AVF type with 66.7%. The wrist region was favorable in subjects (43.1%). Conclusions: Arteriovenous fistulas for hemodialysis are needed and in our center. Radiocephalic AVFs are the most common type. Further study to learn the different aspects of arteriovenous fistula cases is needed to fulfill queries in the local population.